Nuclear Factor Erythroid 2-related Factor 2 (Nrf2) as A Therapeutical Target in Type-2 Diabetes Mellitus: A Review - Asri Hendrawati (The Prodia Education and Research Institute (PERI), 2017)
BACKGROUND: Increasing free radicals and oxidative stress due to chronic hyperglycemia in type-2 diabetes mellitus (DM) promotes the activity of endogenic antioxidative genes. Nuclear factor erythroid 2-related factor 2 (Nrf2) expression and activity are important to regulate the production of endogenic antioxidative enzymes.CONTENT: Normally, Nrf2 is bound by protein Kelchlike ECH-associated protein-1 (Keap1) in the cytosol. Stimulation from oxidative stress causes the release of Nrf2 from Keap1. When activated, Nrf2 enters the nucleus and activates the antioxidant response element (ARE). This will further increase the production of antioxidative enzymes, such as catalase, nitrite oxydase and heme oxygenase-1. The discovery of oxidative stress, as the cause of complications in DM, gives rise to the idea of developing a treatment which can increase the expression and activity of Nrf2, one of which is a flavonoid antioxidant.SUMMARY: Currently, nuclear factor erythroid 2-related factor 2 is an important target in the therapy of DM.KEYWORDS: Nrf2, type-2 diabetes mellitus, endogenic antioxidative enzymes, oxidative stress, antioxidants